STRUKTUR BAGIAN PEMBAHASAN (DISCUSSION SECTION) PADA ARTIKEL PENELITIAN DALAM BAHASA INGGRIS - NK Mirahayuni (Universitas 17 Agustus 1945 Surabaya, 2014)
ABSTRACT. This article reports analysis on the Discussion sections of English research articles published in international journals. The purpose of the analysis is to explore the elements of generic structure contributing to the success of the native English writers in getting their research reports recognised in the international discourse community through international publication. The study adopts Swalesâ€™ (1990) 8-move Model of the Discussion section and involved twenty (20) research articles. The result shows that the texts display the Discussion sections, with variation in their combination with the Result section and the Conclusion section. More importantly, the result also shows that the Discussion sections of the articles under investigation uniformly show the eight functional moves. The findings are expected to enlighten non-native English research article writers of formal and functional features of English research articles.Â Keywords: English research articles, generic structure, discussion sections, Swalesâ€™s 8-move model